PROBLEM BASED LEARNING BERBASIS TPACK TINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Della Pevita Yulia; Siti Dewi Maharani; Firdaus (STKIP Subang, 2024)
This research is motivated by the problem of low learning outcomes of fifth grade students of SD Negeri 112 Palembang in science learning. The purpose of this study was to determine the improvement in student learning outcomes by implementing the Problem Based Learning model based on TPACK. This research was conducted in semester 1 of the 2024/2025 academic year with 25 fifth grade students as research subjects. The research was conducted in 2 cycles, with 4 meetings using qualitative and quantitative descriptive analysis in its data analysis. Observation, documentation and tests are the techniques used in collecting research data. The success criteria set for learning outcomes refer to the Minimum Completeness Criteria, which is 70. The pre-cycle obtained a percentage of learning outcome completion of only 24%. The 1st meeting in cycle I increased to 52% and increased at the 2nd meeting of cycle I to 72%. The 1st meeting of cycle II increased again with the percentage of completion reaching 84% then at the 2nd meeting of cycle II the completion became 100%. The results are in the form of conclusions that show that the TPACK-based PBL model can improve student learning outcomes.